IV.ii.2. Genealogical materials relating to the Crookshank family - Kennedy, Francis M. E. (Francis Malcolm Evory), b. 1869; Young, Geoffrey Winthrop, 1876-1958 (1936)
Various materials pertaining to the history and genealogy of the Crookshank family (Dublin and Kerry branches). Includes family trees, notes on family genealogy and a copy of a Derry Cathedral Registry and grave inscriptions. The Crookshank family was linked to the Kennedy family via Easter Crookshank, mother of Rev. John Pitt Kennedy and paternal grandmother of John Pitt Kennedy.
Keywords: Crookshank family; Genealogy